Exploring the Level of Computer Literacy for Candidates in Higher Education: ICDL Programme at Bahrain Polytechnic - Hana Alqaidoom; Fatima Wali; George K. Toworfe (International Journal of Engineering and Management Research, 2020)
Bahrain Polytechnic is a Higher Education technical institution established in 2008 (by Royal Decree No. 65 for the year 2008). Its main mission is to supply the Bahraini economy with a skilled Bahraini labour force aiming to contribute to economic growth and diversification. The Polytechnic ensures that its values of excellence, learning and innovation are achieved by designing curricula that meet international standards as well as national and individual needs through continuous consultations with the industries and international education institutions. The development of computer and technological literacy is a significant predictor for success in the workplace and is also one of the key skills that the polytechnic provides through its programmes to students and faculty. This paper explores how computer literacy and skills are acquired by educators and students through International Computer Driving License (ICDL) tools employed at Bahrain Polytechnic. The study also considers the challenges that hinder learners from completing the requirements of ICDL. If adequate numbers of faculty and students have already learned basic computer skills, then the question facing the polytechnic is if computer literacy should continue to be taught at all levels. To answer this question, ICDL tests were administered to ascertain the computer literacy level of existing faculty and students. The results of the tests will determine which ICDL tests students and faculty should be placed on in order to address their computer literacy needs.